Efficacy of Emotional Freedom Technique in Reducing Depression and Improving Quality of Life among Stroke Survivors in Pakistan: A Randomized Controlled Trial - Shahzadi, Shazia; Juhary, Ali (2024)
This study evaluated the feasibility and efficacy of Emotional Freedom Techniques (EFT) for reducing post-stroke depression, improving quality of life (QOL), and alleviating caregiver burden among stroke patients in Pakistan. A single-blind randomized controlled trial was conducted with 100 ischemic stroke patients recruited from five rehabilitation hospitals in Islamabad and Rawalpindi. Participants were randomized to EFT plus routine rehabilitation or standard care. Cognitive eligibility was screened using the Mini-Mental State Examination Urdu (MMSE-U). Outcomes were measured at baseline, post-intervention, and follow-up using the Beck Depression Inventory–II (Urdu; BDI-II-U), WHO Quality of Life scale (Urdu; WHOQOL-U), and Burden Scale for Family Caregivers–short (BSFC-s). Subjective Units of Distress (SUDS) were recorded during EFT sessions. Analyses employed paired and independent samples t-tests and repeated-measures ANOVA. Compared with standard care, the EFT group showed significantly greater reductions in depression (BDI-II-U) and greater improvements in QOL (WHOQOL-U) from baseline to post-intervention, with effects sustained at follow-up (all p < .01). Caregiver burden decreased more in the EFT group (BSFC-s; p < .01), and session-by-session SUDS ratings declined, indicating progressive symptom relief. Baseline comparability was established, and sensitivity analyses confirmed robustness of findings. EFT was feasible and produced clinically meaningful improvements in depression, QOL, and caregiver burden when delivered alongside standard rehabilitation in a lower-middle-income setting. Incorporating EFT into multidisciplinary stroke care may address critical psychological needs and enhance recovery. Future studies should explore long-term durability, underlying mechanisms, and implementation strategies across diverse clinical contexts.